Pengaruh Hedonic Shopping Motives, Fashion Involvemen terhadap Impulse Buying E-Commerce Shopee (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Trunojoyo Madura) - Moh. Rony; Bambang Setiyo Pambudi (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
This study aims to determine the effect of hedonic shopping motives, fashion, involvement on impulse buying e-commerce shopee (a study of students from the faculty of economics and business, Trunojoyo Madura University). The method used in this research is purposive sampling, namely the technique of determining the sample by considering certain criteria with a total sample of 97 respondents. The results of this study indicate that 1) Hedonic Shopping Motives variables have a significant effect on impulse buying e-commerce shopee on students of the Faculty of Economics and Business. 2) The fashion involvemen variable has a significant effect on impulse buying of e-commerce shopee for students of the Faculty of Economics and Business.. 3) Variable Hedonic Shopping Motives, fashion involvemen have a significant effect on impulse buying e-commerce shopee on students of the Faculty of Economics and Business. Based on the results of the F test, it can be seen that the value of the Hedonic shopping motivation and fashion involvement variables on impulse buying simultaneously has a significant effect.